KARAKTERISASI LIPID HASIL KULTIVASI MASSAL Spirulina sp. DALAM MEDIA LIMBAH BUDIDAYA UDANG VANAME (Litopenaeus vannamei) - Putri, Ricke Diana; Rusydi, Rachmawati; Ayuzar, Eva; Andriyono, Sapto; Patmawati, Patmawati (Journal of Aquatropica Asia, 2025)
Microalgae is one of the microorganisms that has the potential as raw material in the development of research and technology to produce vegetable oil. Microalgae Spirulina sp. is a microalgae that has the potential to be used as a raw material for biodiesel, which has a fairly high lipid content when compared to other microalgae. However, to produce enough Spirulina sp. biomass, it is necessary to optimize the culture media.  One of the organic materials that can be used as Spirulina sp. culture media is vaname shrimp farming waste (Litopenaeus vannamei). This study aims to utilize vaname shrimp farming waste to minimize costs in mass-scale microalgae cultivation for daily lipid evaluation and biodiesel production. The method used in this study was laboratory experimental method, where observation and primary data collection were conducted on a mass scale. Based on the research results, the highest daily cultivation dry biomass of Spirulina sp. was found on day 4 (four) with a value of 2.29gr/L with a biomass percentage of 7.24%. The highest lipid extracted using soxhlet was on day 4 (four) with a lipid percentage value of 3.73% with a lipid percentage of 0.84% and the highest lipid productivity was also found on day 4 (four) with a value of 0.0854 gr/L. Mass cultivation biomass of Spirulina sp. obtained wet biomass of 13,760 g and dry biomass of 3,220 g. Lipid yield of Spirulina sp. in mass cultivation obtained a weight value of 163.74 g with a percentage of 5.09%. Biodiesel yield of Spirulina sp. in mass cultivation amounted to 101.225 g with a percentage of 61.82%. The quality of Spirulina sp. biodiesel consisted of 4 highest chemical compounds, namely Heptadecane (CAS) n-Heptadecane 41.35%, Hexadecanoid acid, methyl ester 13.03%, Isoppropyl Linoleate 8.91%, and 9,12-Octadecanoid acid (Z,Z)-, methyl ester 6.88%.